2007
DOI: 10.1042/bj20071041
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the formation of a covalent haem–protein link by selection of reductive or oxidative conditions as exemplified by ascorbate peroxidase

Abstract: Raven (2004) J. Am. Chem. Soc. 126, [16242][16243][16244][16245][16246][16247][16248] has shown that the introduction of a methionine residue (S160M variant) close to the 2-vinyl group of the haem in ascorbate peroxidase leads to the formation of a covalent haem-methionine linkage under oxidative conditions (i.e. on reaction with H 2 O 2 ). In the present study, spectroscopic, HPLC and mass spectrometric evidence is presented to show that covalent attachment of the haem to an engineered cysteine residue can al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…The formation of double His-heme cross-links in L79H PCC 6803 under reducing conditions in vitro is of particular interest, as it parallels the double Cys-heme cross-links in the majority of cyts c. Moreover, even when the native cross-link of His117-N ε -2-vinyl-C α was removed, the double mutant of L79H/H117A PCC 6803 can form a single cross-link of His79-N ε -4-vinyl-C α . These observations indicate that each of the double His-heme cross-links form independently in cyanobacteria Hbs, a behavior similar to the double Cys-heme cross-links in cyts c [41][42][43][44][45].…”
Section: C-n Bondmentioning
confidence: 61%
See 4 more Smart Citations
“…The formation of double His-heme cross-links in L79H PCC 6803 under reducing conditions in vitro is of particular interest, as it parallels the double Cys-heme cross-links in the majority of cyts c. Moreover, even when the native cross-link of His117-N ε -2-vinyl-C α was removed, the double mutant of L79H/H117A PCC 6803 can form a single cross-link of His79-N ε -4-vinyl-C α . These observations indicate that each of the double His-heme cross-links form independently in cyanobacteria Hbs, a behavior similar to the double Cys-heme cross-links in cyts c [41][42][43][44][45].…”
Section: C-n Bondmentioning
confidence: 61%
“…Moreover, the thioether bond can form with heme derivatives containing other metals such as Zn 2+ or Mn 2+ [42,43], which provides a convenient strategy for design of artificial metalloproteins containing a non-natural prosthetic group. In agreement with these findings, Metcalfe et al [44] showed that introduction of a Cys (S160C mutation) close to the heme 2-vinyl group in recombinant pea cytosolic ascorbate peroxidase (APX) leads to the formation of a thioether bond, during reconstitution of the apo-protein with heme in vitro under reducing conditions. In addition to the native protein scaffolds of cyt c 552 [41][42][43] and APX [44], thioether bond could also be generated in de novo four-helix bundle proteins by reacting with heme in vitro [45], which opens a way to design functional de novo heme proteins with a non-dissociable heme cofactor.…”
Section: Thioether Bondmentioning
confidence: 68%
See 3 more Smart Citations